Blogging in infectious diseases and clinical microbiology: Assessment of the 'blogosphere' content - Birgand,GJC; Troughton,R; Moore,L; Charani,E; Rawson,TM; Castro-Sanchez,E; Holmes,AH (Infection Control and Hospital Epidemiology, 2017)
Objective.To analyzeinfluential infectious diseases, antimicrobial stewardship, infection control, or medical microbiology blogs and bloggers.Setting. World Wide WebDesign. We conducted a systematic search for blogs in accordance with the PRISMA guidelines in September 2015.Methods.A snowball sampling approach was applied to identify blogs using various search engines. Blogs were eligible if they: 1) focused on infectious diseases (ID), antimicrobial stewardship (AMS), infection control (IC), or medical microbiology (MM); 2) were intended for health professionals, 3) were written in English and updated regularly. We mapped blogs/bloggers characteristics and used an innovative tool to assess their architecture and content. Motivations and perceptions of bloggers and readers were assessed. Results.A total of 88 blogs were identified. 28 (32%) focused on ID, 46 (52%) on MM and 14 (16%) in IC or AMS. Bloggers were mainly male, MD and/or PhD, 32 (36%) posted at least weekly, and 51 (58%) for a research purpose. The aims were considered clear for 23 (26%) blogs, the field covered was broad for 25 (28%), presentation was good for 22 (25%), 51 were easy to read (58%) and 46 included expert interpretation (52%). Among the top 10 blogs (2 equally-ranked), 3 focused on ID, 6 on MM and 2 on IC. Bloggers questioned were motivated by sharing independent expertise/opinion. Readers appreciated the concise messages given on scientific and practical updates.Conclusions.This study describes high level blogs in ID/IC/MM suggesting how bloggers should build/orientate blogs for readers, and highlighting current gaps in topics such as AMS.